Detection of Epl1 and Sm1 genes in Trichoderma spp. antagonists against phytopatogenic fungi - Martínez-Canto, Orlando José; Cristóbal-Alejo, Jairo; Tun-Suárez, José María; Reyes-Ramírez, Arturo (Ecosistemas y Recursos Agropecuarios, 2021)
Trichoderma spp. are used as a method of biocontrol of phytopathogenic that cause agricultural losses. The objective of this work was to identify nine Trichoderma strains, determine the antagonistic capacity against Fusarium oxysporum and Corynespora cassiicola, as well as the genes that encode the elicitors Sm1 and Epl1 of systemic resistance in plants. The antagonistic capacity against phytopathogens was determined through dual confrontations. The molecular identiﬁcation corresponded to T. asperellum (19-31), T. erinaceum (10-15), T. ghanense (21-39) and T. harzianum (18-31, 05E-60, 20-35, 13-01, 01-01, 29-54). Strains 10-15, 19-31 and 05E-60 showed greater mycelial inhibition capacity against F. oxysporum, while the strains 32-09 and 27-08 against C. cassiicola. The volatile metabolites of 27-08, 21-39 and 05E-60 strains inhibited the growth of F. oxysporum. The presence of the Epl1 genes were identiﬁed in 19-31 and 10-15 strains, and Sm1 in 27-08 and 32-09 strains.